Expression of SCD and FADS2 Is Lower in the Necrotic Core and Growing Tumor Area than in the Peritumoral Area of Glioblastoma Multiforme - Jan Korbecki; Klaudyna Kojder; Dariusz Jeżewski; Donata Simińska; Maciej Tarnowski; Patrycja Kopytko; Krzysztof Safranow; Izabela Gutowska; Marta Goschorska; Agnieszka Kolasa-Wołosiuk; Barbara Wiszniewska; Dariusz Chlubek; et al. (Biomolecules, 2020)
The expression of desaturases is higher in many types of cancer, and despite their recognized role in oncogenesis, there has been no research on the expression of desaturases in glioblastoma multiforme (GBM). Tumor tissue samples were collected during surgery from 28 patients (16 men and 12 women) diagnosed with GBM. The effect of necrotic conditions and nutritional deficiency (mimicking conditions in the studied tumor zones) was studied in an in vitro culture of human brain (glioblastoma astrocytoma) U-87 MG cells. Analysis of desaturase expression was made by qRT-PCR and the immunohistochemistry method. In the tumor, the expression of stearoyl–coenzyme A desaturase (SCD) and fatty acid desaturases 2 (FADS2) was lower than in the peritumoral area. The expression of other desaturases did not differ in between the distinguished zones. We found no differences in the expression of SCD, fatty acid desaturases 1 (FADS1), or FADS2 between the sexes. Necrotic conditions and nutritional deficiency increased the expression of the studied desaturase in human brain (glioblastoma astrocytoma) U-87 MG cells. The obtained results suggest that (i) biosynthesis of monounsaturated fatty acids (MUFA) and polyunsaturated fatty acids (PUFA) in a GBM tumor is less intense than in the peritumoral area; (ii) expressions of SCD, SCD5, FADS1, and FADS2 correlate with each other in the necrotic core, growing tumor area, and peritumoral area; (iii) expressions of desaturases in a GBM tumor do not differ between the sexes; and (iv) nutritional deficiency increases the biosynthesis of MUFA and PUFA in GBM cells.